Changes in salicylic acid and polyamine contents following powdery mildew infection of near-isogenic Thatcher-based wheat lines carrying different Lr genes - Pál, Magda (Acta Biologica Szegediensis, 2011)
Changes in endogenous salicylic acid and polyamine contents were investigated following infection with powdery mildew in four near-isogenic Thatcher-based wheat lines. Although the infection could not affect the quantum efficiency of photosystem 2 after 7 days in the investigated genotypes, significant changes were observed in the levels of salicylic acid and polyamines of inoculated plants. Powdery mildew infection caused decrease in salicylic acid content after 3 days, but on the 7th day of infection increased it significantly in line carrying Lr33 gene. Infection also increased the salicylic acid content after 7 days in line carrying Lr19 gene, while the other genotypes were hardly affected. Infection increased the levels of cadaverine, spermidine and spermine in the free form, as well as the levels of spermidine and spermine in the conjugated form. Infection could not affect either of the polyamines associated with various macromolecules (bound form). It was concluded that although salicylic acid and polyamines have important role in plant responses and defence mechanisms during biotic stress, there is no correlation between pathogen induced changes in the levels of them and the level of tolerance to powdery mildew of the investigated four wheat lines.